Dietary Supplementation With Bacillus subtilis Promotes Growth and Gut Health of Weaned Piglets - Tian, Zhilong; Wang, Xiaodan; Duan, Yehui; Zhao, Yue; Zhang, Wenming; Azad, Md. Abul Kalam; Wang, Zhanbin; Blachier, Francois; Kong, Xiangfeng (Frontiers in Veterinary Science, 2021)
This study was conducted to investigate the effects of dietary supplementation with Bacillus subtilis (B. subtilis) on growth and gut health of weaned piglets. A total of 160 piglets were randomly assigned into four groups: control group (a basal diet), BS-A group (a basal diet supplemented with B. subtilis A at 1 × 109 CFU/g feed), BS-B group (a basal diet supplemented with B. subtilis B at 1 × 106 CFU/g feed), and BS-C group (a basal diet supplemented with B. subtilis C at 1 × 106 CFU/g feed). All groups contained five replicates with eight piglets per replicate. On days 7, 21, and 42 of the trial, blood plasma, intestinal tissues, and digesta samples were collected to determine cytokine concentrations, intestinal morphology, gut microbiota composition and metabolic activity, and the expression of genes related to gut physiology and metabolism. The results showed that dietary B. subtilis supplementation improved the size of small intestinal villi and decreased the diarrhea rates of weaned piglets (P < 0.05). Firmicutes, Bacteroidetes, and Tenericutes were the most dominant microflora in piglets’ colon contents whatever the trail group and time of analysis. Dietary BS-C supplementation increased the relative abundance of Anaerovibrio and Bulleidia and decreased the ratio of Clostridium and Coprococcus compared with the control group (P < 0.05). In addition, dietary B. subtilis supplementation increased (P < 0.05) the indicators of intestinal health including plasma levels of interleukin (IL)-2 and IL-10, as well as the colonic levels of short-chain fatty acids. Furthermore, dietary B. subtilis supplementation also increased (P < 0.05) the expression of genes involved in metabolic pathways related to intestinal microbiota maturation. In conclusion, these findings suggest that dietary B. subtilis supplementation efficaciously promotes growth performance, decreases diarrhea incidence in piglets, and ameliorates several indicators of intestinal health through the modulation of gut microbiota composition and metabolic activity in weaned piglets.